River transition: a Costa Rica and Honduras comparative analysis of water quality and community management stages in river basins - Navarro, Nuria; Suárez-Serrano, Andrea; Golcher, Christian; Flores, Pablo; de Anguita, Pablo Martínez (Frontiers in Conservation Science, 2026)
This article explores the potential existence of a conceptual “River Transition Curve” model in water quality and community-based river management, using Costa Rica and Honduras as case studies. It draws parallels to the well-established Forest Transition Curve, which describes how forest cover changes over socio-economic development stages: initial deforestation, stabilization, and eventual reforestation. It is proposed that a similar pattern may exist for rivers, linking water quality and river health to economic development and land use change. Therefore, understanding the temporal evolution of rivers, comparable to forest transitions, could inform more effective watershed management policies. In the context of Central America, rivers face significant degradation due to pollution, overexploitation, deforestation, climate change, and infrastructure modifications like channelization. This study characterized water quality in the Liberia River (Costa Rica) and Tela watersheds (Honduras), identifying key management challenges. Furthermore, it conducted citizen perception sounding surveys on water management and held water education workshops in schools and communities within these watersheds. The results indicated chronic fecal contamination in all rivers studied in Honduras and Costa Rica, extending to coastal zones. This finding underscores the need for enhanced wastewater infrastructure management and stricter enforcement of water quality standards to protect environmental and community health. Surveys and workshops suggested that targeted water education significantly enhances community knowledge and empowerment, which are critical drivers for improved participatory water governance. Rather than proposing direct policy prescriptions, this study offers conceptual and empirical insights to inform future policy development and support more integrated and sustainable water governance in the region. It also highlights the need for further validation of the proposed river transition curve and emphasizes the importance of community engagement and water education for the protection of river ecosystems in Central America.